2016
DOI: 10.3390/md14010019
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products from Marine Fungi—Still an Underrepresented Resource

Abstract: Marine fungi represent a huge potential for new natural products and an increased number of new metabolites have become known over the past years, while much of the hidden potential still needs to be uncovered. Representative examples of biodiversity studies of marine fungi and of natural products from a diverse selection of marine fungi from the author’s lab are highlighting important aspects of this research. If one considers the huge phylogenetic diversity of marine fungi and their almost ubiquitous distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
154
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(159 citation statements)
references
References 91 publications
2
154
0
3
Order By: Relevance
“…The systematic search of substances from marine fungi, their structure elucidation, and biological activities have established quite a number of new substances in recent years [1,2,3]. In the present study, for the first time, three benzocoumarins were found to express significant inhibition of GSK-3β.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The systematic search of substances from marine fungi, their structure elucidation, and biological activities have established quite a number of new substances in recent years [1,2,3]. In the present study, for the first time, three benzocoumarins were found to express significant inhibition of GSK-3β.…”
Section: Discussionsupporting
confidence: 50%
“…Marine fungi have been found to be an important source for new bioactive metabolites in recent years [1,2,3]. They reveal a wide spectrum of structurally different compounds with a wide range of biological activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As methods for sample collection, identification, and culturing technologies of deep-sea microorganisms have advanced significantly in recent years, a shift of foci from shallow water to the deep sea for natural product chemists has come along [2]. During studies on the diversity of fungi in the deep Mediterranean Sea and also on sponges, in particular in Tethya aurantium [3], a valuable tool for the identification of fungal isolates proved to be the combination of morphological criteria and the comparison of the ITS1-5.8S-ITS2 fragment sequences [3,4]. In particular, the sequence information gave valuable additional information for the phylogenetic evaluation of the investigated isolates.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the sequence information gave valuable additional information for the phylogenetic evaluation of the investigated isolates. Our studies with sediments from the deep Mediterranean Sea have shown the dominance of representatives of Aspergillus and Penicillium (almost half of all isolates) together with isolates from 10 other genera, including strain LF657 as a single isolate (out of a total of 43) of Biscogniauxia [4]. This Biscogniauxia isolate was obtained from sediments of the Herodotes Deep (2800 m depth) in the Mediterranean Sea and properties of this fungus and the production of metabolites are reported in the present study.…”
Section: Introductionmentioning
confidence: 99%